2022
DOI: 10.1007/s11356-022-23129-y
|View full text |Cite
|
Sign up to set email alerts
|

Source identification and health risks of nitrate contamination in shallow groundwater: a case study in Subei Lake basin

Abstract: Nitrate pollution in groundwater has become a global concern as it can affect the drinking water quality and human health. In this paper, an extensive hydrochemical investigation and health risk were performed in the Subei Lake basin where shallow groundwater is the main available drinking water resource for residents. The prevalent pollutant, nitrate (NO 3 -), has been identi ed based on descriptive statistical method and box and whisker plots, and most of the other parameters of groundwater samples meet wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Concerning most physiochemical parameters, no significant differences are reported between samples corresponding to all experimental sites (Table 3). Li et al (2022) reported similar limits and content hierarchy in groundwater cations (Ca, Mg), iron, and major anions (HCO 3 − , SO 4 2− , Cl − , NO 3 − ), but higher contents in F − and NH 4 + in studies performed to emphasize the quality parameters of the groundwater collected from different sites [48]. Suthar et al (2009) reported greater groundwater contamination in rural areas of India due to mineral and organic fertilization practices, compared to our results, concerning nitrates(NO 3 − ), chlorine (Cl − ), and sulfates (SO 4 2− ) [49].…”
Section: Physiochemical Characterization Of the Groundwater Qualitymentioning
confidence: 94%
“…Concerning most physiochemical parameters, no significant differences are reported between samples corresponding to all experimental sites (Table 3). Li et al (2022) reported similar limits and content hierarchy in groundwater cations (Ca, Mg), iron, and major anions (HCO 3 − , SO 4 2− , Cl − , NO 3 − ), but higher contents in F − and NH 4 + in studies performed to emphasize the quality parameters of the groundwater collected from different sites [48]. Suthar et al (2009) reported greater groundwater contamination in rural areas of India due to mineral and organic fertilization practices, compared to our results, concerning nitrates(NO 3 − ), chlorine (Cl − ), and sulfates (SO 4 2− ) [49].…”
Section: Physiochemical Characterization Of the Groundwater Qualitymentioning
confidence: 94%
“…In addition, excessive nitrate in the environment leads to algal blooms that, in turn, cause eutrophication and hypoxia in surface water bodies, such as rivers, lakes, and even oceans (Bijay-Singh and Craswell, 2021;Górski et al, 2019;Zhang et al, 2021;Wang et al, 2018;Scavia and Bricker, 2006). Water resource pollution by nitrate is primarily attributed to intensive agricultural fertilizer application (Li et al, 2023;Rahmati et al, 2015;Gu et al, 2013;Zhang et al, 2014). Excessive fertilization results in the down-leaching of nitrate from the soil through the unsaturated zone to the groundwater.…”
Section: Introductionmentioning
confidence: 99%